Tandem mass spectrometry identification and LC-MS quantification of intact cytokinin nucleotides in K-562 human leukemia cells - Béres, Tibor; Zatloukal, Marek; Voller, Jiří; Niemann, Percy; Gahsche, Marie Christin; Tarkowski, Petr; Novák, Ondřej; Hanuš, Jan; Strnad, Miroslav; Doležal, Karel (Analytical and bioanalytical chemistry, 2010)
We describe here a new reversed-phase high-performance liquid chromatography with mass spectrometry detection method for quantifying intact cytokinin nucleotides in human K-562 leukemia cells. Tandem mass spectrometry was used to identify the intracellular metabolites (cytokinin monophosphorylated, diphosphorylated, and triphosphorylated nucleotides) in riboside-treated cells. For the protein precipitation and sample preparation, a trichloroacetic acid extraction method is used. Samples are then back-extracted with diethyl ether, lyophilized, reconstituted, and injected into the LC system. Analytes were quantified in negative selected ion monitoring mode using a single quadrupole mass spectrometer. The method was validated in terms of retention time stabilities, limits of detection, linearity, recovery, and analytical accuracy. The developed method was linear in the range of 1-1,000 pmol for all studied compounds. The limits of detection for the analytes vary from 0.2 to 0.6 pmol.
Keywords: Cytokinins; hmotnostní spektrometrie; Mass Spectrometry; Molecular Structure; molekulární struktura; lidé; Nucleotides; tandemová hmotnostní spektrometrie; Chromatography, Liquid; Cell Line, Tumor; Tandem Mass Spectrometry; chromatografie kapalinová; nukleotidy; nádorové buněčné linie; cytokininy; Humans